Angularly Cascaded Long-Period Fiber Grating for Curvature and Temperature Detection - Anping Xiao; Jie Du; Qiang Ling; Yao Chen; Zhengtian Gu; Haiyun Chen; Zhangwei Yu; Barerem-Melgueba Mao; Zuguang Guan; Daru Chen (Sensors, 2023)
A high-sensitivity curvature sensor with dual-parameter measurement ability based on angularly cascaded long-period fiber grating (AC-LPFG) is proposed and experimentally demonstrated, which consists of two titled LPFGs (TLPFGs) with different tilt angles and the same grating period. AC-LPFG was fabricated by using a deep ultraviolet laser and an amplitude-mask in our laboratory. The experimental results show that simultaneous measurement of curvature and temperature can be achieved by monitoring the wavelengths of two resonant peaks for different TLPFGs. The two peaks show opposite shifts with increasing curvature and has a maximum curvature sensitivity of 16.392 nm/m−1. With the advantages of low cost, high sensitivity, and dual-parameter measurements, our sensor has more potential for engineering applications.